Acute Bullous Irritant Contact Dermatitis Following Topical Application of Potentilla erecta and Plantago lanceolata - Emine Sarcan; Ali Kablan; Tuba Şafak; Burcu Doğan (Academic Journal of Health, 2026)
Although herbal products are widely used, inappropriate or unsupervised application may result in serious cutaneous reactions. We report a case of severe bullous irritant contact dermatitis that developed following the topical application of a mixture of Potentilla erecta and Plantago lanceolata. A 51-year-old woman presented to the emergency department with painful bullous lesions involving both elbows and the plantar surfaces of both feet approximately 24 hours after applying the herbal preparation. The absence of sun exposure, mucosal involvement, systemic manifestations, and laboratory abnormalities, together with a detailed history of herbal exposure, were pivotal in establishing the diagnosis. The lesions resolved completely following wound care, systemic corticosteroid therapy, and supportive care. This case highlights the importance of considering phytodermatitis in the differential diagnosis of patients presenting with burn-like bullous skin lesions and underscores the critical role of obtaining a detailed history of herbal exposure in establishing an accurate diagnosis and guiding appropriate management.